Successful management of a colchicine overdose with plasmapheresis: a case report - İbrahim Halil Toksul; İbrahim Altundağ; Rıza Çete; Ziad Kazzi; Semih Korkut; Aynur Şahin (Toxicology Communications, 2023)
AbstractAn overdose of colchicine can be lethal due to its narrow therapeutic index. We aimed to describe the successful management of a large intentional overdose with plasmapheresis therapy. A 32-year-old female presented to the Emergency Department with nausea, vomiting, and dizziness eight hours after intentionally ingesting 0.9 mg/kg colchicine in tablet form. She was treated with plasmapheresis and supportive therapy. The only abnormality in four days of observation was one-day transient lymphopenia (0.82 x 109/L).